STUDI FIKIH DI PERGURUAN TINGGI: Kajian Model Pembelajaran Andragogi - Rosidin, Rosidin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Constraints often encountered by lecturers in educating students is still attached pedagogical mentality like students of secondary education; has not moved on andragogical mentality like a college student. These constraints can be found in the context of basic principles of andragogy. As a library research, this paper examines the data sources in the form of literature relevant to Islamic law (fiqh) studies and andragogy (adult education). The study results in six models of andragogical learning for the development of Islamic law (fiqh) courses in higher education. First, the learning model of â€œlearn how to knowâ€ that emphasizes aspects of epistemology to increase studentsâ€™ curiosity (need to know). Second, independent learning model that emphasizes student activeness in learning. Third, experiential based learning model, especially literature and field research practice, to foster inclusive thinking. Fourth, actual life-based learning model, either related to worship or muamalat. Fifth, contextual learning model to find alternative solutions to real life problems from the perspective of Islamic law (fiqh). Sixth, the learning model to develop studentsâ€™ intrinsic motivation.